HUBUNGAN AKTIVITAS FISIK DENGAN FUNGSI KOGNITIF PADA LANSIA DI DESA TANJUNGAN KEC. KEMLAGI KAB. MOJOKERTO - Triwibowo, Heri; Puspitasari, Kiki (S1 Keperawatan, 2014)
Cognitive function generally is affected by several factors, for instance: physical health, physical activity, mental health, social activity, and social support associated with cognitive impairment. Sport or physical activity probably an important non-pharmacological can be done beneficially for cognitive function and reducing the risk of cognitive impairment. This study aims to prove the relationship between physical activity and cognitive on elderly in Tanjungan village Kec. Kemlagi of Mojokerto. The research design on this study uses analytical analysis with crosssectional approach. The samples being studied were 30 elderly in Tanjungan village Kec. Kemlagi of Mojokerto. Data were collected using questionnaire, physical activity using GPPAQ and cognitive function using MMSE. Based on data obtained 11 respondents (36,7%) of elderly were quite active on physical activity, 9 respondents (30%) of elderly were inactive on physical activity and 1 respondent (3,3%) of elderly was active on physical activity. The result of Spearmen Rho test was ï² = 0,000 with ï¡=0,05 in consequence ï²